THE EFFECT OF ECONOMIC STATUS AND MOTOR MATURITY ON THE PERFORMANCE OF FUTSAL ATHLETES AT SMK CINTA KASIH TZU CHI: THE ROLE OF SELF-EFFICACY AS MEDIATION - Galih Yoga Purnama; Endang Rini Sukamti; Fauzi; Abdul Alim (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of economic status and motor maturity on futsal athletes performance through the mediation of self-efficacy. The research design employed a quantitative cross-sectional approach using a census method on 30 male athletes from SMK Cinta Kasih Tzu Chi. Data analysis utilized mediation regression based on the Hayes PROCESS Macro Model 4 with bootstrapping procedure 5,000 times to ensure the accuracy of astimates in a small sample size. Instrument reliability was confirmed through Cronbach's Alpha coefficient of 0.89 (self-efficacy) and an the Intraclass Correlation Coefficient (ICC) of 0.91 (performance). The analysis results showed that economic status did not have significant direct effect on performance (β=0.082; p=0.651) but exerts a significant indirect effect through self-efficacy (full mediation; IE=0.231; 95% CI [0.054; 0.487]). Motor maturity significantly affects performance both directly (β=0.389; p=0.004) and indirectly through self-efficacy (partial mediation; IE=0.175; 95% CI [0.031; 0.389]). The overall model exhibits high predictive power (R²=0.658). These findings confirm that self-efficacy is an essential cognitive mechanism capable of mitigating limitations in socioeconomic and biological capital to achieve tangible performance in futsal.